What is conservative and revolutionary about the “conservative revolution”? Argument-level evidence from three thinkers - Pankakoski, Timo (Frontiers in Political Science, 2022)
This article reassesses the concept of “conservative revolution” by textual and argumentative analysis of the work of Arthur Moeller van den Bruck, Ernst Jünger, and Hans Freyer – three prominent thinkers of the “conservative revolution” in interwar Germany. Rather than problematically conflating conservative and revolutionary elements into abstract ideological positions, which produces the “paradox” of conservative revolution observed by several scholars, I propose we must take seriously the argumentative context. What, exactly, did they mean by the apparently contradictory idea? This, I posit, can only be comprehended by analyzing the elements of conservatism and revolution in the original sources and with regard to the broader argumentative framework in which the notion of “conservative revolution” emerged. First, the article analyzes the three thinkers' idea of a future-oriented, politically creative, and genuinely historical conservatism in opposition to mere backward-looking unhistorical reactionism. Second, it addresses the question of revolution as a destructive political means for conservative ends and shows how Moeller, Jünger, and Freyer linguistically constructed a continuity between the failed revolution of 1918 and the anticipated conservative revolution. The three authors spoke of continuous movement, the conservation of energy, and volcanic forces to argue for a seamless continuity between the two revolutions, thereby using the proximity of the ideologically opposing revolt for their own argumentative ends. This situatedness gives rise to doubts about the generalizability of the conservative revolution idea beyond its context of emergence: although similar ideas emerged elsewhere in the era and have been revived lately among the New Right, the particular historical dynamics of the concept of conservative revolution hinders its applicability and popular appeal in later settings that lack comparable widely shared experiences of revolutionary events.